Application of beethoven’s classical music therapy: A case study on patients with auditory hallucinations at RSJD Dr. Arif Zainudin Surakarta - Sukotjo, Ivanda Andinar; Oktaviana, Wita; Nugroho, Andi (Science Midwifery, 2025)
Auditory hallucinations are a perceptual disorder in which individuals respond to stimuli that are not present, yet perceived as real. This case study aimed to evaluate the effectiveness of Beethoven classical music therapy in reducing the intensity of auditory hallucinations among patients with schizophrenia at Dr. Arif Zainudin Surakarta Mental Hospital. The therapy was applied as a complementary non-pharmacological intervention to help manage hallucination symptoms. A pre-test and post-test design was used with five patients diagnosed with schizophrenia who experienced auditory hallucinations. Each patient received Beethoven classical music therapy in a series of scheduled sessions. The measurement instrument was the Auditory Hallucination Rating Scale (AHRS). Validity testing was conducted using confirmatory factor analysis (RMSEA = 0.00; CFI = 0.994), while reliability was assessed using Cronbach’s alpha (α = 0.61). The AHRS measures the frequency, duration, conviction, and impact of hallucinations on daily activities. Pre- and post-therapy data were analyzed using the Shapiro Wilk normality test, followed by a paired t-test. Results indicated a significant reduction in AHRS scores (p = 0.000; p < 0.05) across all patients after receiving the therapy, indicating a positive effect in reducing hallucination intensity.